ANALISIS RASIO KEUANGAN PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2010-2013 - Hamidi, Hamidi (Universitas Riau Kepulauan, 2014)
The financial statements are very important for the company. Due to the financial statements can be used as a tool to assess and measure the financial performance of companies in each period. The financial statements consist of a balance sheet, income statement, statement of changes in capital, the report notes to the financial statements and cash flow statements. The aim of the research in this thesis is to determine the level of financial analysis ratios on Telecommunications companies listed in Indonesia Stock Exchange. The object of research by the author ie 6 telecommunication companies listed in Indonesia Stock Exchange (IDX). Types of data used are secondary data from the financial statements of documents obtained from the web IDX. The author uses qualitative methods and techniques of comparative figures in the financial statements.